2021
DOI: 10.1038/s41467-021-26054-9
|View full text |Cite
|
Sign up to set email alerts
|

Programmable nano-reactors for stochastic sensing

Abstract: Chemical reactions of single molecules, caused by rapid formation or breaking of chemical bonds, are difficult to observe even with state-of-the-art instruments. A biological nanopore can be engineered into a single molecule reactor, capable of detecting the binding of a monatomic ion or the transient appearance of chemical intermediates. Pore engineering of this type is however technically challenging, which has significantly restricted further development of this technique. We propose a versatile strategy, “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 98 publications
(123 reference statements)
1
40
0
Order By: Relevance
“…All nanopore measurements in this study were carried out as previously reported. 33 A self-assembled lipid bilayer consisting of DPhPC separated the measurement device into two chambers. Each chamber contained 500 μL of buffer of 1.5 M KCl, 10 mM HEPES, pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All nanopore measurements in this study were carried out as previously reported. 33 A self-assembled lipid bilayer consisting of DPhPC separated the measurement device into two chambers. Each chamber contained 500 μL of buffer of 1.5 M KCl, 10 mM HEPES, pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
“…However, owing to the technical complexity associated with the chemical engineering of the pore lumen, direct discrimination of enantiomers has been only rarely reported with nanopores. 29−32 Programmable nanoreactors for stochastic sensing (PNRSS) 33 is a versatile, recently developed strategy to probe single-molecule reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenylboronic acid (PBA) is known to form covalent bonds reversibly with 1,2 or 1,3-diols 39 . Previously, the introduction of PBA to the nanopore lumen was successfully applied to the detection of various cis-diol-containing analytes such as saccharides 40 , epinephrine and Remdesivir 41 . However, a hetero-octameric MspA nanopore containing a single PBA adaptor has not been reported previously and nanopore identification of a large variety of epigenetically modified nucleoside monophosphates (NMPs) has also never been reported.…”
mentioning
confidence: 99%
“…The proposed system would be potentially useful for medical applications if this system will integrate into a commercially available nanopore sequencer such as MinION (Oxford Nanopore Technologies). Moreover, several biological nanopores other than αHL have also been used for nanopore sensing. , The nanopore decoding will have the potential to apply to the different types of nanopores.…”
Section: Discussionmentioning
confidence: 99%